Leadership in an Ageing Society and the Brain: Applying Neuroscience to Leadership - Katja Debelak; Sandra Penger; Barbara Grah (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
"What makes a great leader?" This question has been on the minds of scientists, philosophers, professionals, and others around the globe for centuries. Many theories and models have been proposed to answer the question, but none has fully captured leadership as a dynamic and constantly evolving attitude. In the last 20 years, technological advancements have helped neuroscientists understand the human brain better. With the help of ground-breaking insights in neuroscience, the leadership enigma has a convincing answer rooted in a specific and very tangible source: the brain. This paper aims to increase awareness around the impact of the brain on leadership behaviour in an aging society by presenting secondary research of available scientific theory. In particular, this paper aims to provide an overview and assess the brain-based leadership models and recent approaches to highlight the possible ways to boost the leadership brain and enhance performance. The paper also points out the ethical issues arising from brain enhancement in leadership and leaders' awareness of the possible broad social consequences that neuro leadership might bring.
Keywords: D87; L29; M14; O15; 330; leadership; brain; neuroscience; neuro leadership; brain-based; neuroethics; ageing society